Tajikistan: University Challenges and the Professoriate - Kataeva, Zumrad (International Higher Education, 2017)
Tajikistan's higher education sector has experienced significant challenges after the breakup of the Soviet Union followed by the civil war of 1992-1997. The situation and status of the professoriate throughout the Post-Soviet space has deteriorated, as salaries and professional development opportunities have spiraled downward. Liberalization of the economy and the promise of higher education access have led to a rise in the demand for higher education. Higher education institutions have had to hire lesser-prepared faculty as those more seasoned or talented among the professoriate left for the private sector or migrated abroad. Today, the compensation of faculty members in Tajikistan is not enough to cover living costs, forcing them to use a variety of strategies to survive. They work as translators, consultants, or private tutors. The Tajik higher education system needs to work on establishing policies and opportunities to better support the profession, especially if institutions of higher education are eager to compete in the growing global educational marketplace.